Protected - Jenkins, Jerry B.; LaHaye, Tim F.; Fabry, Chris (Wheaton, Illionios : Tyndale House Publishers, 2005)
"A frightening face shows up on the security cameras at the Wisconsin hideout. Vicki puts herself and the others at risk, contacting someone on the outside. Will it be the end of the Trib Force in Wisconsin? At the same time, Judd and Lionel are determined to make it back to their friends in the States but end up getting in the greatest danger they've seen yet. Sam watches as deadly bombs hurtle toward Petra. He wonders if Tsion Ben-Judahs' predictions about the safety of Petra are correct."--Back cover.
Protected is a special edition compilation of the following Left behind : the kids titles: #32 : War of the dragon ; #33 : Attack on Petra ; #34 : Bounty hunters.
Keywords: Christian life -- Fiction; Fiction